FAST-TRACK HIP AND KNEE ARTHROPLASTY (LITERATURE REVIEW) - A. M. Ageenko; M. A. Sadovoy; O. V. Shelyakina; M. A. Ovtin (Travmatologiâ i Ortopediâ Rossii, 2017)
In the present paper the authors discuss the history of fast-track formation, its development and current status. Fast-track advantages in comparison to other rehabilitation options are analyzed. The focus is placed on methods of accelerated rehabilitation after total hip and knee arthroplasty in the leading European and American clinics. Fast-track protocols of surgical centers of Denmark and Hospital for special surgery in the US are described, factors that determine time of hospital stay after total hip and knee arthroplasty are considered, predictors of hospital stay and patients satisfaction after the surgery are examined. The paper reflects the results of the comparison of frequency of thromboembolic and other complications as well as readmission rate after traditional rehabilitation and after fast-track. The paper considers fast-track in bilateral total knee replacement. The authors conclude that further research on acceleration of rehabilitation and reduction of hospital stay after total hip and knee arthroplasty needs to be focused on the optimization of pain relief, especially after discharge, blood preservation techniques, supplementation of fluids loss and strengthening of muscles. Literature analysis demonstrated that the implementation of the Protocol for accelerated recovery after joint arthroplasty in Russia is at an insufficient level. Data of foreign multicenter studies during recent years indicate a high efficacy and safety of this technique in different groups of patients.